2021
DOI: 10.1016/j.jaci.2020.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular changes during peanut-induced allergic reactions in human subjects

Abstract: The funders of the study had no role in study design, data collection, data analysis, data interpretation, or writing of the report. The corresponding author had full access to all the data in the study and had final responsibility for the decision to submit for publication. Disclosure of potential conflict of interest: M. H. Shamji has received grants from ALK-Abell o, Regeneron, Merck, ASIT Biotech.sa, and the Immune Tolerance Network and has received personal fees from ASIT Biotech.sa, ALK-Abell o, Allergop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 31 publications
1
28
1
2
Order By: Relevance
“…For example, the allergic reaction may have caused a disturbance in normal postural circulatory reflexes, akin to the blunting of postural reflexes which is often observed during anaesthesia 19 . Orthostatic hypotension is associated with a decrease in heart rate variability, 20,21 and previous studies in both children and adults have reported reduced heart rate variability following food‐induced allergic reactions, independent of severity 18,22 . Thus, these episodes could potentially represent a more mild form of the postural decompensation seen in some cases of fatal anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the allergic reaction may have caused a disturbance in normal postural circulatory reflexes, akin to the blunting of postural reflexes which is often observed during anaesthesia 19 . Orthostatic hypotension is associated with a decrease in heart rate variability, 20,21 and previous studies in both children and adults have reported reduced heart rate variability following food‐induced allergic reactions, independent of severity 18,22 . Thus, these episodes could potentially represent a more mild form of the postural decompensation seen in some cases of fatal anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Food-allergic patients present with a marked diversity by reactivity profiles ( 15 ). Clinical symptoms range from mild to severe (severity score) as does eliciting doses (sensitivity score) and time to reaction onset are highly variable ( 16 , 17 ). The estimated dose likely to trigger reactions in 10% of a study population (ED 10 ) vary also for specific foods (eg, peanut 11 mg; shrimp 12.8 g protein) ( 18 ).…”
Section: Type-i Hypersensitivity To Foodmentioning
confidence: 99%
“…Effective adrenaline causes vasoconstriction and bronchodilation, increases myocardial contractility and inhibits mast cell degranulation 3 . Plasma extravasation equivalent to one third of the circulating blood volume can occur within minutes in severe reactions 5 ; however, venous return is significantly compromised even in those without overt haemodynamic compromise 6 . Intravenous fluid support is therefore necessary, both to treat shock and to maintain adequate circulatory volume to optimize adrenaline delivery.…”
Section: Figurementioning
confidence: 99%